The Rise of Mental Health Nursing A History of Psychiatric Care in Dutch Asylums, 1890-1920 - Boschma, Geertje (Amsterdam University Press, 2003)
Examining the relations between the rise of scientific psychiatry and the emergence of mental health nursing in Dutch asylums, this study analyses the social relationships of class, gender and religion that structured asylum care in the Netherlands around 1900. Drawing on archival collections of four Dutch asylums, the book highlights the gendered nature of mental health nursing politics. Seeking to model the asylum after the forceful example of the general hospital, psychiatrists introduced new somatic treatments and designed mental nurse training which aimed at creating a nursing staff skilled in somatic care. The training system, based on the projected image of the civilized, middle-class female nurse, bringing competence and compassion to the care of the mentally ill, created new opportunities for women, while at the same time restricting the role of men in nursing. Capturing the contradictory realities of hospital-oriented asylum care, the book illustrates the social complexity of the care of the mentally ill and forms an important addition to the historiography on European psychiatry.